Effect of arsenic trioxide on rat hepatocarcinoma and its renal cytotoxicity - Wang, Shao-Shan (World J Gastroenterol, 2003)
AIM: To study the effect of arsenic trioxide (As(2)O(3)) on rat experimental hepatocarcinoma and its renal cytotoxicity. METHODS: The hepatocarcinoma model was established by diethaylnitrosamine perfusion in stomach of 120 Wistar rats, and the treatment began at the end of 20 weeks. Before the treatment, the rat models were randomly divided into 5 groups. In the treatment groups, three doses of As(2)O(3) were injected into rat abdominal cavity, the total time of drug administration was 4 weeks. Cisplatin control or the blank group was injected into abdominal cavity with equal amount of cisplatin or saline at the same time, respectively. On the 7(th), 14(th) and 28(th) day after the treatment, the hepatocarcinoma nodules were obtained and the morphologic changes of hepatocarcinoma cells were observed under light and electron microscopes; Immunohistochemistry (S-P methods) was employed to detect the expression of bcl-2, bax and PCNA in hepatocarcinoma tissues; flow cytometry (TUNEL assay) was used to detect the apoptosis of liver cancer cells and the change of cytokinetics. On the 28(th) day, the kidneys were obtained and their histologic changes were observed under light microscope, and immunohistochemistry (SP stain) was also employed to detect the expression of bcl-2 and PCNA. Cisplatin and saline solution were used as the control. RESULTS: As(2)O(3) could induce the apoptosis of rat liver cancer cells and exhibited typical morphologic changes. The incidence of apoptosis of hapatocarcinoma cells was elevated (P = 0.001). The elevation was the most higher in the group of middle-dose of As(2)O(3) (1 mg·kg(-1)), significantly higher than that of the other arsenic groups and the controls (P = 0.001). Large dose of As(2)O(3) (5 mg·kg(-1)) was able to arise the incidence of apoptosis, but also produced a large amount of necrosis and inflammatory reaction. Middle dose of As(2)O(3) dramatically increased the cell number in G2/M phase (P = 0.0001), and apoptosis happened apparently. The expression of bcl-2 and bax was related to the dose of As(2)O(3). With the up-regulation of apoptotic incidence, the ratio of bcl-2/bak decreased. But the incidence of apoptosis was not the highest status and the ratio of bcl-2/bax was at the lowest when the highest-dose of As(2)O(3) was used. There was significant difference among the PCNA indexes (PCNA L1) of the five groups. Of them, three arsenic groups all showed decrease of different degrees, and this down-regulation was most obvious in group A. There was significant difference among the three groups (P = 0.016). Under the light microscope, the rat kidney in the cisplatin group exhibited tubular epithelium swelling and degeneration, protein casts in collecting tubules; While all arsenic groups didn’t show the significant changes (P = 0.013). In the arsenic groups, the expression of bcl-2 in the renal tubular epithelium was increased (P = 0.005), no obvious changes happened to PCNA L1. But in the group of cisplatin, the PCNA L1 increased significantly (P = 0.001). CONCLUSION: As(2)O(3) can induce apoptosis of rat hepatocellular carcinoma cells. And there is optimum dose; too high dose will induce the cytotoxic effect, while certain dose of As(2)O(3) is able to block the cell cycle at G2/M phase. As(2)O(3) had the most remarkable influence on G2/M cells, and it can also induce apoptosis to cells at other phases. As(2)O(3) can restrain the proliferation of rat hepatocellular carcinoma cells, in a dose-time dependent manner. Compared with cisplatin, As(2)O(3) didn’t show obvious renal toxicity, which was related to the increasing expression of bcl-2 in renal tubular epithelium, the inhibition of apoptosis and the anti-oxidation effects.